2005
DOI: 10.1111/j.1542-474x.2005.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Automatic Defibrillator Implantation Trial–Cardiac Resynchronization Therapy (MADIT‐CRT): Design and Clinical Protocol

Abstract: The planned MADIT-CRT trial is designed to determine if CRT-D will reduce the risk of mortality and HF events by approximately 25% in subjects with ischemic (NYHA class I-II) and non-ischemic (NYHA class II) cardiomyopathy, left ventricular dysfunction (EF ≤ 0.30), and prolonged intraventricular conduction (QRS duration ≥ 130 ms). A.N.E. 2005;10(4)Supplement:34-43MADIT; cardiac resynchronization therapy; heart failure Heart failure (HF) with its associated morbidity and mortality remains a major unresolved pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 201 publications
(126 citation statements)
references
References 21 publications
2
120
0
4
Order By: Relevance
“…As cardiac resynchronization therapy is considered for an expanded population of CHF patients 12,13 and leftsided pacing is considered as an option for pacemakerindicated patients (potentially without ICD backup), 36 the effect of these pacing modalities on the incidence of ventricular tachyarrhythmias must be systematically studied and mechanistically understood. Strategies to prospectively predict the proarrhythmic potential of LV epicardial pacing need to be developed, and therapy accordingly individualized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As cardiac resynchronization therapy is considered for an expanded population of CHF patients 12,13 and leftsided pacing is considered as an option for pacemakerindicated patients (potentially without ICD backup), 36 the effect of these pacing modalities on the incidence of ventricular tachyarrhythmias must be systematically studied and mechanistically understood. Strategies to prospectively predict the proarrhythmic potential of LV epicardial pacing need to be developed, and therapy accordingly individualized.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Other studies, however, have demonstrated the potential for proarrhythmia. 9 -11 As CRT becomes more widely adopted and is considered for an expanded population of heart failure (HF) patients, 12,13 the effect of this pacing modality on the incidence of ventricular tachyarrhythmias must be thoroughly understood. This review attempts to summarize the current information on proarrhythmia in resynchronization therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Echocardiography recordings were analyzed off-line at the Brigham and Women's Hospital, Boston, Massachusetts as an independent echocardiography core laboratory [11]. Echocardiography investigators analyzing the images were blinded to clinical characteristics, treatment assignment, or outcomes.…”
Section: Echocardiography Methodsmentioning
confidence: 99%
“…All eligible patients met the guideline criteria for ICD [13]. Patients were excluded with certain clinical characteristics, as described previously [11]. One hundred and ten hospital centers from North America and Europe participated in this international multicenter trial.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation